Oral and oropharyngeal cancer: time from first symptoms to treatment initiation and associated factors - Adriana Aparecida Silva da COSTA; Patrícia Carlos CALDEIRA; Alexandre Andrade SOUSA; Jacqueline Domingues TIBÚRCIO; Leonardo de Queiroz Gomes BELLIGOLI; Viviane Bigodeiro dos SANTOS; Pedro Messeder Caldeira BRETAS; Louise Lanna NUNES; Severino Correia do PRADO NETO; Gustavo Waldolato SILVA; João Marcos Arantes SOARES (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of this study was to evaluate the time elapsed from first symptoms to the treatment of oral and oropharyngeal cancer (OOC) and to identify variables associated with treatment delay. This is an observational study with retrospective and prospective data collection. Patients with a diagnosis of OOC seen at the Head and Neck Surgery outpatient clinic of a Brazilian public hospital were included and followed up to treatment initiation. Participants answered a questionnaire for the collection of socioeconomic, demographic, cultural, and clinical information, as well as information about the time elapsed from first symptoms to the first appointment with a head and neck surgeon. Time to treatment was classified into four intervals: 1- first symptoms to first medical appointment; 2- first medical appointment to specialized medical care; 3- specialized medical care to preparation for treatment; and 4- preparation for treatment to treatment initiation. Bivariate statistics were computed. Out of 100 participants, nine died before treatment. Mean time to treatment was 217 days. Highest mean time was observed for interval 2 (94 days), followed by interval 1 (63 days), interval 4 (39 days), and interval 3 (21 days). At interval 1, a longer time was associated with severe alcohol consumption, severe smoking, and family history of cancer. At interval 2, the delay was associated with appointment with a general practitioner, clinical diagnosis of disease other than cancer, and antibiotic prescription. At interval 4, delay in treatment was associated with surgical treatment. Patients with OOC experience delays from symptom onset to treatment initiation. The longest interval was associated with professional delay, followed by patient delay in help-seeking.